PENINGKATAN HASIL BELAJAR MEMBACA TEKS NARATIVE DENGAN MELALUI PERMAINAN “RUMMY CARDS” - Siti Komariyah (Education Journal : Journal Educational Research and Development, 2018)
Reading narrative text means that is purposed to understand the content of a narrative text or story, narrative text is based on in order of events or phenomenon where is the main character in that story get the problem until in the top of the crisis and then get the end of the resolution, the story can be happy ending or sad ending. This text has a purpose to entertain the reader or listener. The result of the research show that by the game of rummy card can improve the learning outcome of reading narrative text of student class VIII E SMP Negeri 5 Trenggalek in the second semester academic year 2010/2011. The percentage of completeness of classical learning activity in cycle I reached 55% with grade average grade 64, while the percentage of completeness of classical learning activity in cycle II reach 95% with grade average grade 77. There is an increase of classical learning activity 30%.